Strategi Pembelajaran Problem Solving, Gaya Belajar Kolb, dan Hasil Belajar Mekanika Rekayasa - Tri Kuncoro; Amat Mukhadis (Universitas Negeri Malang, 2013)
Abstract: Problem-solving Teaching Strategy, Kolb Learning Styles, and Learning Achievement. This quasi experimental study was intended to investigate the differences in learning achievement in Mechanical Engineering II Course between students taught using problem - solving strategy, taking their learning styles into considerations. The independent variable of problem-solving strategy includes open-ended (Psoe) and closed- ended (Psce), whereas the moderating variable of learning style consists of diverging, converging, and assimilating styles. The subjects were randomly selected from Mechanical Engineering II classes, resulting in 68 students joining Psoe strategy and 64 joining PSce strategy. The data obtained from problem - solving test method revealed that students with Psoe strategy outperformed those with Psce moderated by the learning styles of diverging, assimilating, converging and accommodating. Abstrak: Strategi pembelajaran Problem Solving, Gaya Belajar Kolb, dan Hasil Belajar Mekanika Rekayasa. Penelitian ini bertujuan menguji perbedaan hasil belajar mahasiswa yang mengikuti pembelajaran dengan strategi problem solving dan gaya belajar diverging style, converging style dan assimilating style. Penelitian ini merupakan penelitian kuasi eksperimen dengan rancangan kelompok kontrol non-ekuivalen (nonequivalent kontrol group design). Subjek berjumlah 167 mahasiswa Teknik Sipil peserta kuliah Mekanika Rekayasa II. Data dikumpulkan dengan tes, dan dianalisis dengan Analisis Varian. Hasilnya menunjukkan bahwa strategi pembelajaran open ended problem solving lebih unggul daripada strategi closed ended problem solving pada kelompok gaya belajar diverging, assimilating, converging dan accommodating. Gaya belajar converging lebih unggul daripada gaya belajar diverging pada pembelajaran open ended problem solving dan closed ended problem solving.